Subrogated assets in place of own assets - The intervention of both spouses in the acquisition act - MAGALHÃES JESUS, Andreia Madalena (Revista Jurídica Portucalense, 2023)
Marriage brings with it property effects that require their own regulation. When we refer to the community of acquired property regime, we quickly like to think about the constituted assets: the assets of each of the spouses and the common assets. Article 1723 of the CC makes it possible to subrogate assets in place of own assets. We are therefore faced with situations in which the acquisition is made after the marriage, for consideration, but such assets, once the formalities provided for in the aforementioned article have been fulfilled, retain the quality of their own assets. For this contribution, it is important to address the formalities in paragraph c), more specifically with regard to the intervention of both spouses in the acquisition act. The main questions to which we intend to provide our contribution are: are the requirements set out in paragraph c) cumulative? What are the positions of jurisprudence, and what is the role of the Uniform Jurisprudence Judgment 12/2015? Can we overcome the lack of mention as to the origin of the money or goods? What if the acquirer's spouse refuses to intervene in the act to confirm that the money used is the acquiring spouse's own money? To answer these questions, we resort to a jurisprudential and doctrinal analysis, ending with some brief considerations.